The roles of movement and coat proteins in the transport of tobamoviruses between plant cells - Kan, Yumin; Citovsky, Vitaly (Frontiers in Plant Science, 2025)
Tobamovirus is a large group of positive-sense, single-stranded RNA viruses that cause diseases in a broad range of plant species, including many agronomically important crops. The number of known Tobamovirus species has been on the rise in recent years, and currently, this genus includes 47 viruses. Tobamoviruses are transmitted mainly by mechanical contact, such as physical touching by hands or agricultural tools; and some are also transmitted on seeds, or through pollinator insects. The tobamoviral genome encodes proteins that have evolved to fulfill the main conceptual task of the viral infection cycle - the spread of the invading virus throughout the host plant cells, tissues, and organs. Here, we discuss this aspect of the infection cycle of tobamoviruses, focusing on the advances in our understanding of the local, i.e., cell-to-cell, and systemic, i.e., organ-to-organ, virus movement, and the viral and host plant determinants of these processes. Specifically, we spotlight two viral proteins—the movement protein (MP) and the coat protein (CP), which are directly involved in the local and systemic spread of tobamoviruses—with respect to their phylogeny, activities during viral movement, and interactions with the host determinants of the movement process.